Distributed Acoustic Sensing as a Distributed Hydraulic Sensor in Fractured Bedrock. Issue 9 (28th August 2020) - Becker, M. W.; Coleman, T. I.; Ciervo, C. C.
Abstract: Distributed acoustic sensing (DAS) was originally intended to measure oscillatory strain at frequencies of 1 Hz or more on a fiber optic cable. Recently, measurements at much lower frequencies have opened the possibility of using DAS as a dynamic strain sensor in boreholes. A fiber optic cable mechanically coupled to a geologic formation will strain in response to hydraulic stresses in pores and fractures. A DAS interrogator can measure dynamic strain in the borehole, which can be related to fluid pressure through the mechanical compliance properties of the formation. Because DAS makes distributed measurements, it is capable of both locating hydraulically active features and quantifying the fluid pressure in the formation. We present field experiments in which a fiber optic cable was mechanically coupled to two crystalline rock boreholes. The formation was stressed hydraulically at another well using alternating injection and pumping. The DAS instrument measured oscillating strain at the location of a fracture zone known to be hydraulically active. Rock displacements of less than 1 nm were measured. Laboratory experiments confirm that displacement is measured correctly. These results suggest that fiber optic cable embedded in geologic formations may be used to map hydraulic connections in three‐dimensional fracture networks. A great advantage of this approach is that strain, an indirect measure of hydraulic stress, can be measured without beforehand knowledge of flowing fractures that intersect boreholes. The technology has obvious applications in water resources, geothermal energy, CO2 sequestration, and remediation of groundwater in fractured bedrock. Plain Language Summary: A technology developed for measuring vibrations on fiber optic cable, distributed acoustic sensing, is used to measure strain in bedrock in response to pumping and injection. This technology is extremely sensitive to dynamic strain, measuring displacements approaching the size of a water molecule. Field tests showed that fluid‐induced strain in rock exhibits complex geometry. The technology can be used to better understand flow in bedrock, optimize geothermal energy extraction, and identify leakage from subsurface injection systems. Key Points: Distributed acoustic sensing (DAS) can accurately measure dynamic bedrock strain at low frequency The distributed strain measurement identified fluid stimulation of hydraulically connected bedrock fractures Measurement of hydromechanical response in wells provides a robust tool for establishing bedrock plumbing in groundwater and geothermal systems